METHOD OF PROGNOSTICATION OF HYDRAULIC EFFICIENCY OF GAS PIPELINES - Грудз, Володимир Ярославович; Якимів, Микола Мирославович (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY. Number, 2019)
Method of determination of coefficient of hydraulic efficiency of gas pipelines is offered taking into account all types of power charges on transporting of gas. We show influence of different types of power resources of gas stream on estimation of hydraulic efficiency. It is set, that no account of losses of internal energy brings errors over of calculation of coefficient of hydraulic efficiency of gas pipeline not only to the increase but also to distortion of picture of his sentinel of trend.